Combined transcriptome and widely targeted metabolome analysis reveals the potential mechanism of HupA biosynthesis and antioxidant activity in Huperzia serrata - Wu, Hao; Shen, Yu; Zou, Fen; Yao, Shiqing; Chen, Yaling; Yang, Huilin; Luo, Xiangdong (Frontiers in Plant Science, 2024)
Huperzia serrata is a traditional Chinese herb that has gained much attention for its production of Huperzine A (HupA). HupA has shown promise on treating Alzheimer's disease (AD). However, the biosynthetic pathway and molecular mechanism of HupA in H. serrata are still not well understood. In this study, wild H. serrata (WH) and in vitro H. serrata thallus (HT) were used to investigate the HupA biosynthesis and antioxidant mechanisms by integrative analysis of the metabolome and transcriptome. The results showed that HT exhibited higher antioxidant activity and lower cytotoxicity compared to WH. Through hierarchical clustering and qRT-PCR verification, 7 important enzyme genes and 13 transcription factors (TFs) related to HupA biosynthesis were detected. Among them, the average |log2FC| value of CYP (Cytochrome P450) and CAO (Copper amine oxidase) was the largest. Metabolomic analysis identified 12 metabolites involved in the HupA biosynthesis and 29 metabolites related to antioxidant activity. KEGG co-enrichment analysis revealed that tropane, piperidine and pyridine alkaloid biosynthesis were involved in the HupA biosynthesis pathway. Furthermore, the phenylpropanoid, phenylalanine, and flavonoid biosynthesis pathway were found to regulate the antioxidant activity of H. serrata. The study also identified seven important genes, including PrAO (primary-amine oxidase), related to the regulation of antioxidant activity.Based on the above joint analysis, the biosynthetic pathway of HupA and potential mechanisms of antioxidant in H. serrata was constructed. These findings provide valuable insights into the HupA biosynthesis mechanism and the H. serrata thallus medicinal value.